The Effect of Antioxidants of -Tocopherol on the Characteristic of Mechanical, Thermal, and Morphology Properties of Polypropylene-Montmorillonite (PP-MMT) Nanocomposites - Julinawati, Julinawati; Rahmi, Rahmi; MZ., Kartika; Mustafa, Irfan; Suryati, Suryati (Universitas Syiah Kuala, 2023)
The purpose of this study was to determine the effect of -tocopherol on the mechanical, thermal, and morphological properties of polypropylene-montmorillonite (PP-MMT) nanocomposites. The preparation of polypropylene-montmorillonite (PP-MMT-AO) nanocomposites was carried out on PP compositions; PP-g-MA; MMT-octadecyl amine; AO is 80;10;10;5 and the PP-MMT nanocomposite composition is PP; PP-g-MA; MMT-Octadecyl amine: 80;10;10. The SEM results showed that polypropylene, MMT, and the antioxidant -tocopherol could be exfoliated and intercalated to produce compatible nanocomposites. The mechanical and thermal test results showed that the PP-MMT-AO nanocomposite had higher mechanical properties and thermal stability than the PP-MMT nanocomposite. Based on the FTIR test and degradation test on PP-MMT and PP-MMT-AO films which were carried out for up to 15 days and 30 days showed that the PP-MMT-AO nanocomposite against UV light was given, this shows that -Tocopherol can prevent oxidation reactions polypropylene.